The Effect of Product Quality, Responsiveness and Promotion on Customer Satisfaction at Pt Global Graha Sarana Abadi - Jeffrey Jeffrey; Rosinta Romauli Situmeang; Christopher Christopher (Jurnal Mantik, 2021)
The research location was conducted at PT Global Graha Sarana Abadi. PT Global Graha Sarana Abadi is a company engaged in the retail trade of household electrical appliances and lighting equipment. At this time the company is experiencing a decline in customer satisfaction which can be seen from the complaints submitted to the company. In general, product quality is closely related to the product's ability to withstand durability and the ability of the product to carry out its functions. Responsiveness is the ability of employees to serve customers owned by employees. Fast and maximum service will be a separate assessment for employees in the company. Promotion is a product introduction process carried out by the company by providing certain benefits to prospective customers who will buy the product. The theoretical limitation will be limited through marketing management in product quality, responsiveness, promotion and customer satisfaction. This study uses a simple random sampling formula with the Slovin formula. With a population of 136 customers and 30 people to test the validity and a sample of 101 customers. Quantitative research was chosen as the data collection method. The analysis used in the form of multiple analysis methods, determination testing and testing simultaneously test (28,190 > 3.09) and partial test (2,779 > 1,984), (5,529 > 1,984) and (4.794 > 1,984). The results showed that product quality, responsiveness and promotion were positive and significant with a coefficient with a ratio of 44.9%.